Глава 1. Реформа цивільного судочинства в Україні та необхідність її проведення - Фурса, Світлана Ярославівна; Фурса, Євген Іванович (Цивільний процес: теорія і практика. Концепції вчених з удосконалення законодавства про цивільне судочинство. Монографія, 2023)
Іn the scientific work, the authors made the first warning that during the recodification of civil legislation, it is first necessary to create a new version of the Civil Code of Ukraine (hereinafter – the Civil Code) and only after that start work on the project of the Civil Procedure Code of Ukraine (hereinafter – the Civil Procedure Code of Ukraine). However, work on the improvement of the Central Committee can be carried out in parallel and coordinated with the work on the improvement of the Central Committee, but this is extremely difficult to ensure. The authors believe that when starting work on a new edition of the CPC, one should first form its new structure with the systematization of relevant material, since the provisions of the current CPC are not laid out consistently.The judicial system of Ukraine should work within the limits of the law, but the state should find measures of influence on offenders and the demonstration of the will of the authorities is needed not for a short demonstration period, but on a permanent basis.Access to justice in civil proceedings in Ukraine should be discussed through the prism of whether a person with a minimum wage can protect his rights in court. Obviously not, because he cannot pay the large court fee. And this provision does not meet the requirements of Articles 3 and 55 of the Constitution of Ukraine, nor international standards, in particular, Articles 6 and 13 of the European Convention on the Protection of Rights and Fundamental Freedoms, since low-income citizens are, in fact, deprived of the right to access to justice and protection of their rights. Therefore, it is necessary to revise not only the norms of the Code of Civil Procedure, but also the laws of Ukraine «On court fees» and «On free legal aid».The right to appeal to the court for protection should not depend on the level of the plaintiff’s financial condition, if Ukraine is a rule of law state, but should be guaranteed to every person who needs it.Оne of the main issues of the new CPC project should be coordination and interaction of certain types of civil court proceedings, in particular, such as injunctive and claim, therefore the authors proposed ways to solve these issues.The authors paid a lot of attention to the analysis of minor disputes, the criteria for classifying certain categories of cases as minor. The impossibility of classifying labor disputes as minor is substantiated with reference to the Constitution of Ukraine. A reasoned opinion was expressed regarding the impracticality of paying the same court fee, which is paid in both «significant» and minor cases, taking into account the order of their consideration. It is proposed to improve the civil justice system taking into account Recommendation No. R (95) 5 of 02.07.1995 of the Committee of Ministers of the Council of Europe.list of shortcomings of the current legislation on civil procedure is given. When applied by the court, they should be considered as an abuse of law by the court. If the CPC does not record the court’s duty to respond to every argument of the party, then all other norms are a camouflage for the legally guaranteed arbitrariness of the judicial branch of government, no matter what proceeding we are talking about. If a person is limited in the right to be heard, then what judicial procedure can we talk about...Certain debatable issues are pointed out, which are subject to discussion and resolution when creating a new version of the CPC. The authors believe that the given arguments and arguments should be submitted for public discussion in order for the new version of the Code of Civil Procedure to be better, not worse, than the current regulatory act.But when implementing the idea of updating and recodifying the Central Committee, making changes to the Central Committee will become objectively inevitable, and not only to the Central Committee. The same applies to Ukraine’s accession to the EU, as it will be necessary to bring the CPC into compliance with the recommendations existing in the European community. no But you cannot make random amendments to the adopted draft law, and the introduction of fragmentary amendments quite often leads to an imbalance of the regulatory act as a whole.